Upaya Pemerintah Indonesia dala menbgevakuasi WNI pasca krisis Mesir - Pungki Citra Dewi (HI 13 UMY 037, 2013)
A lot of Indonesian citizen stay in Egypt with many purposes, such as study, work, and ambassador. Egypt is education city and save country to work. But the peace is broken by revolution at 2011, January 25. After that, there is crisis situation with many victims. The situation caused many countries evacuated their citizen from Egypt, include Indonesia. Based on research, it is known that Indonesian government has done two kinds of evacuation. First, direct evacuation to the region which has direct crisis. Second, indirect evacuation to the region which has indirect crisis by asked the citizen to collect in safe house, and then flied to Indonesia. There are many constraints in Indonesian citizen evacuation process, such as: 1) Psychologist constraint; consists of communication constraint, students evacuation denied, and far location evacuation. 2) Government constraint; government reactive action, political constraint, and transportation constraint to evacuate the citizen. All of the constraints made the evacuation gone slowly. But the evacuation still success, proved by the fact that there are 6 evacuated group. Every group consist of 400 citizens. Totally there is 2.400 citizens evacuated.